Pengembangan Alat Latihan Scanning untuk Latihan Keterampilan Menerima Bola pada Sepak Bola Usia Muda - Dwi Kurnia Shandy; Weda; Rendhitya Prima Putra; Ilaika Kafka Priyadana; Rais Ihsan Raya (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study designs Scapa Pro as an innovative solution to enhance passing quality through the integration of field-scanning drills. Utilizing the systematic phases of the ADDIE model, this tool was developed to sharpen players' spatial awareness prior to receiving the ball. Field findings confirm that the implementation of Scapa Pro has a positive impact on players' ability to identify passing options swiftly and accurately. Practically, this research offers a new reference in basic technique development capable of improving on-field performance efficiency.